A First-Order Optimal Zero-Forcing Beamformer Design for Multiuser MIMO Systems via a Regularized Dual Accelerated Gradient Method - Li, Bin; Dam, Hai Huyen Heidi; Cantoni, Antonio; Teo, Kok Lay (IEEE Communications Society, 2015)
A first-order zero-forcing beamformer design is proposed in this letter for MU-MIMO systems under per-antenna power constraints (PAPC). By forming the regularized dual problem, first-order methods can be applied. To achieve the limit convergence rate of first-order methods, an accelerated method is introduced to solve the regularized dual problem. Simulation results are provided to show the effectiveness of the proposed method.